Institutionalization of Ḥisbah: A Means to Achieve Peaceful and Credible Elections in Nigeriaa: - Yahya Shaykh Ahmad; Yusuph Dauda Gambari (Universitas Negeri Jakarta, 2024)
The important pillar of the so-called democracy, which is an election, has been violent and marked by problems ranging from rigging, vote buying, illegal printing of voters’ cards, illegal possession of ballot boxes, stuffing of ballot boxes, underage voting, and falsification of election results to manipulation of results in Nigeria. Thus, the Nigerian experience with elections since independence has been quite challenging despite that conduct of elections is the only acceptable means through which the citizens of a democratic country can choose their representatives. This paper therefore appraises one of the important institutions introduced by Islam to cater to the promotion of good and prohibition of evil (ḥisbah) in society with a view to underline the importance of its institutionalization to stem the menace of electoral malpractices in Nigeria. The reason is that the institution of ḥisbah was successfully deployed during the classical periods of Islam to arrest cases of cheating in the marketplaces as well as the public dispositions. The study employs a qualitative research methodology based on literature review. Data collected from a variety of books, periodicals, and other sources, were then subjected to analysis. The findings of the study reveal that the electoral malpractices that characterized the past elections will be overcome and credible elections will be achieved if ḥisbah is institutionalized in the country. It concludes that the advocacy for its introduction in Nigeria is not an attempt to Islamize the country but a yearning call for the injection of an efficient institution that can change the narrative of electoral fraud in Nigeria as it was practiced in the Northern part of the country before its colonization.